Case Report: Management of a patient with Sheehan’s syndrome presenting with anxiety and depression - Liu, Hongxia; Chen, Rensheng; Feng, Chengzhen; Zhu, Di; Luo, Chao; Chen, Guanming; Chen, Yuehua (Frontiers in Endocrinology, 2025)
Sheehan’s syndrome is a rare and under-recognized disorder that may be encountered in a variety of clinical settings. The diagnosis of the condition is challenging due to its rarity and the fact that it is often overlooked in differential diagnoses. In addition, there are no characteristic clinical features or routine laboratory tests that immediately inform the diagnosis. We report the case of a 50-year-old woman diagnosed with an anxiety-depressive state, who had marked and progressive symptoms, which resolved more rapidly following treatment with escitalopram oxalate and recurred after discontinuation of the medication. Further examination revealed abnormalities in hormone levels and pituitary augmentation MRI, based which the patient was finally diagnosed with Sheehan’s syndrome. This case emphasizes the rarity of patients with Sheehan’s syndrome presenting with anxiety and depression, thereby presenting a diagnostic challenge to clinicians. The objective of this case report is to emphasize the necessity for heightened awareness among healthcare professionals regarding patients with rare clinical presentations and the significance of timely and collaborative treatment strategies.